Self-identified strategies to manage intake of tempting foods: cross-sectional and prospective associations with BMI and snack intake - Jennifer Gatzemeier; Laura L Wilkinson; Menna J Price; Michelle D Lee (Public Health Nutrition, 2024)
Abstract